Incidence and risk factors for COVID‐19 associated candidemia (CAC) in ICU patients. Issue 5 (10th March 2022) - Kayaaslan, Bircan; Kaya Kalem, Ayşe; Asilturk, Dilek; Kaplan, Betul; Dönertas, Gülen; Hasanoglu, Imran; Eser, Fatma; Korkmazer, Ruveyda; Oktay, Zeynep; Ozkocak Turan, Isıl; Erdem, Deniz; Bektas, Hesna; et al.
Abstract: Background: Critically ill COVID‐19 patients have a high risk for the development of candidemia due to being exposed to both well‐defined classical risk factors and COVID‐19‐specific risk factors in ICU. Objectives: In this study, we investigated the incidence of candidemia in critically COVID‐19 patients, and the independent risk factors for candidemia. Patients/methods: COVID‐19 patients hospitalised in ICU during 1‐year period (August 2020 to August 2021) were included. Clinical and laboratory characteristics of all COVID‐19 patients, applied treatments, and invasive procedures that may predispose to candidemia were recorded. Results: Of 1229 COVID‐19 patients, 63 developed candidemia. Candidemia incidence rate was 4.4 episodes per 1000 ICU days. The most common species was Candida albicans (52.3%). Only 37 patients (58.7%) received antifungal therapy. The presence of central venous catheter (OR 4.7, 95% CI 1.8–12.2, p < .005), multifocal candida colonisation (OR 2.7, 95% CI 1.4–5.2, p < .005), a prolonged ICU stay (≥14 days) (OR 1.9, 95% CI 1.08–3–37, p < .05), the absence of chronic lung disease (OR 0.4, 95% CI 0.1–0.9, p < .05) and the absence of corticosteroid use (OR 0.3, 95% CI 0.14–0.52, p < .0001) were significantly associated with candidemia. Conclusions: Our study filled the knowledge gap in the literature about the impact of COVID‐19‐associated risk factors for the development of candidemia. The classical risk factors for candidemia had a significant effect on candidemia, and contrary to expectations, corticosteroids had a protective effect against the development of candidemia. The results of these studies showing interesting effects of corticosteroids in critically ill COVID‐19 patients should be confirmed by further studies.